Fostering Higher Growth and Employment in the Kingdom of Morocco - World Bank (Washington, DC: World Bank, 2012)
This book identifies the binding constraints to growth of Morocco. It applies an innovative procedure known as "growth diagnostic" and has a central finding. The Moroccan economy suffers from a too slow process of structural transformation for achieving higher growth, especially for its exports that face unfavorable external shocks arising from competitor countries in the main markets for Moroccan exports. This process of so-called "productive diversification" requires that Morocco enhance its competitiveness.